The Influence of Independent Commissioners and Audit Committee on Tax Avoidance - Rosida Ibrahim; Nika Esti Rahayu; Asri Primasiwi (Journal of Social Science and Humanities, 2025)
This study was conducted in order to empirically test the influence of independent commissioners and audit committee on tax avoidance. The population in this study in all LQ45 companies listed on the Indonesia Stock Exchange (IDX) in 2022-2024. The research sample was obtained by the Purposive Sampling method of 23 companies or as many as 69 companies in 5 research periods. The analysis tool used is EViews-12, with technical data analysis in the form of selected modeling tests (fixed effect models), classic assumption tests (normality tests, multicollinearity tests and heteroscedasticity tests), panel data regression analysis, and hypothesis test (T test, F test, and coefficient determination test). In this study Tax Avoidance was measured using Effective Tax Rate (ETR) which is to divide the tax burden with profit before tax. ETR results that are close to number 1 show the more obedient to the company in fulfilling its tax obligations. Independent Commissioner is measured by dividing the number of independent commissioners in the company with the entire number of Board of Commissioners. The Audit Committee is measured by the total number of audit committees in the company. The results showed that independent commissioners had a significant effect on the positive direction on tax avoidance and the audit committee had a significant effect on tax avoidance in a positive direction. Based on the results of the study shows that the independent commissioners and audit committees have functioned well in conducting supervision so that tax avoidance can be minimized.